TAX MORALE DETERMINANTS IN PORTUGAL - Sá, Cristina; Martins, António; Gomes, Carlos (European Scientific Journal, ESJ, 2015)
Tax morale has been recognized as the key to understand the levels of compliance achieved in most countries in the world. We applied a structural equation model (SEM) to gain a better understanding about the factors shaping tax morale of Portuguese taxpayer’s. Our purpose was to analyze through SEM the direct effects of political democratic system, political participation, religiosity, individual satisfaction, trust in others and institutional trust on tax morale. A sample of 1,553 Portuguese individuals representative of Portuguese population obtained from European Values Study (EVS), carried out in 2008-2010 was used. The results confirmed that Portuguese taxpayers´ tax morale is influenced by taxpayers trust on institutions like government, parliament and the judicial system, by political participation and by the belief that democracy is a good political system for governing the country. Tax morale is also influenced by individual´s satisfaction, by religiosity and by societal behavior (trust in others). We concluded that tax morale is strongly influenced by political and psychological factors.